Influence of compatibilizing system on morphology, thermal and mechanical properties of high flow polypropylene reinforced with short hemp fibers. (February 2015) - Panaitescu, Denis Mihaela; Vuluga, Zina; Ghiurea, Marius; Iorga, Michaela; Nicolae, Cristian; Gabor, Raluca
Abstract: Simultaneous influence of polypropylene-graft-maleic anhydride (MAPP) and silane-treated hemp fibers (HF) on morphology, thermal and mechanical properties of high-flow polypropylene (PP) modified with poly[styrene-b-(ethylene-co-butylene)-b-styrene] (SEBS) was studied in this paper. The addition of SEBS reduced the efficiency of MAPP in PP composites with HF, thus silane-treated fibers (HFs) were used to improve polymer–fiber interface. Thermal stability of HF was improved after silane treatment and less than 2% weight loss was observed at 240 °C in composites with 30 wt% HF. Better dispersion of fibers and better efficiency in enhancing static and dynamic mechanical properties of PP, doubling its strength and stiffness were observed in composites with treated fibers compared to untreated ones. High ability to absorb and dissipate energy and well-balanced strength and stiffness were showed by PP modified with SEBS and MAPP containing 30 wt% HFs. These composites were studied as an alternative to conventional PP/glass fibers composites for injection molding of small to medium auto parts.